The Influence of Product Quality and Service Quality on Customer Satisfaction at Jogja Printing Madison - Aji, Revo Yustitia; Soebiantoro, Ugy (Jurnal Ekonomi Balance, 2023)
The development of an increasingly developing era makes a lot of competition between competitors in various sectors. Starting from the industrial sector to retail. One that is experiencing intense competition in today's era is a company engaged in the printing sector. This happened in the printing sector when there were several new companies that came with renewable technology, causing the companies that were first engaged in the printing sector to experience a decline in sales. To survive against other competitors, entrepreneurs in the printing sector must be more creative and innovative to be able to compete. There are several ways that several companies engaged in the printing sector can use to stay afloat in the face of new competitors like today. For example, by providing a price cut, improving the quality of their products, or improving the quality of the services they provide to customers. The measurement scale used in this study uses a linkert scale using a non-probability technique aside from the accidental sampling method for sampling. Researchers used samples from the existing population of 55 respondents. The data collection was carried out by researchers using a questionnaire distribution system with Partial Least Square (PLS) analysis techniques. The results of the study indicate that product quality and service quality have a significant positive effect on customer satisfaction at the printing press Jogja printing in Madiun